An analytical solution for radioactive MHD flow TiO2–Fe3O4/H2O nanofluid and its biological applications. Issue 1 (31st December 2022) - Elangovan, K.; Subbarao, K.; Gangadhar, Kotha
Abstract : The measuring instrument for medical investigation and bio-screening depending on organic labelling and nanoparticle identification is active research. An analytical approach is used to investigate mass and heat transfer properties on an unstable movement of the Casson nanofluid beyond the stretched exterior under the influence of induction heat. In addition to this, a simple perturbation method is used to determine the flow of dominating mathematical statements, while titanium oxide and ferrous oxide nanoparticles are drooping in H2 O-based nanofluid. The velocity increases with the temperature slip. The magnetic field can raise the ending layer surface to slow down the velocity. The friction factor grows with the amplification in the nanoparticle volume fraction, and it lessens with the rise of the thermal slip. The thermal convection effect of nanoparticles reveals that the temperature distribution increases, which helps to damage cancer cells in the process of medicine distribution.